Anti-Inflammatory and Antioxidant Chinese Herbal Medicines: Links between Traditional Characters and the Skin Lipoperoxidation “Western” Model - Jose M. Prieto; Guillermo R. Schinella (Antioxidants, 2022)
The relationship between lipid peroxidation and inflammation has been accepted as a paradigm in the field of topical inflammation. The underlying biochemical mechanisms may be summarised as unspecific oxidative damage followed by specific oxidative processes as the physio pathological response in skin tissues. In this experimental review we hypothesise that the characteristics attributed by Traditional Chinese Medicine (TCM) to herbal drugs can be linked to their biomolecular activities within the framework of the above paradigm. To this end, we review and collect experimental data from several TCM herbal drugs to create 2D-3D pharmacological and biochemical spaces that are further reduced to a bidimensional combined space. When multivariate analysis is applied to the latter, it unveils a series of links between TCM herbal characters and the skin lipoperoxidation “Western” model. With the help of these patterns and a focused review on their chemical, pharmacological and antioxidant properties we show that cleansing herbs of bitter and cold nature acting through removal of toxins—including P. amurense, Coptis chinensis, S. baicalensis and F. suspensa—are highly correlated with strong inhibition of both lipid peroxidation and eicosanoids production. Sweet drugs—such as A. membranaceus, A. sinensis and P. cocos—act through a specific inhibition of the eicosanoids production. The therapeutic value of the remaining drugs—with low antioxidant or anti-inflammatory activity—seems to be based on their actions on the Qi with the exception of furanocoumarin containing herbs—A. dahurica and A. pubescens—which “expel wind”. A further observation from our results is that the drugs present in the highly active “Cleansing herbs” cluster are commonly used and may be interchangeable. Our work may pave the way to a translation between two medical systems with radically different philosophies and help the prioritisation of active ingredients with specific biomolecular activities of interest for the treatment of skin conditions.